1999
DOI: 10.1001/archinte.159.11.1205
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Prognostic Significance of Repeated Blood Pressure Measurements in the Elderly

Abstract: , MD; and general practitioners of SPAA Background: In young and middle-aged people, both systolic (SBP) and diastolic (DBP) blood pressure have a continuous, strong, and independent relationship with subsequent cardiovascular morbidity and mortality. These relationships are not well documented in older people and, until now, studies in the elderly do not provide homogeneous results on the importance of DBP compared with SBP as a cardiovascular risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…The most consistent vital sign found to predict adverse clinical events was the systolic blood pressure. This fi nding is consistent with growing evidence from the medical literature that the systolic blood pressure is replacing the diastolic pressure as the most important vital sign in assessing risk of cardiovascular events, [11][12][13][14][15][16][17] especially in an aging population. 12,13 The strength of the association varied among outcome events we modeled, but overall an elevation of 10 mmHg in blood pressure was associated with an increase in risk ranging from 6% for stroke or myocardial infarction (fi rst or recurrent) to 13% for chronic renal insuffi ciency.…”
Section: Risk Of Adverse Events For Hypertensionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most consistent vital sign found to predict adverse clinical events was the systolic blood pressure. This fi nding is consistent with growing evidence from the medical literature that the systolic blood pressure is replacing the diastolic pressure as the most important vital sign in assessing risk of cardiovascular events, [11][12][13][14][15][16][17] especially in an aging population. 12,13 The strength of the association varied among outcome events we modeled, but overall an elevation of 10 mmHg in blood pressure was associated with an increase in risk ranging from 6% for stroke or myocardial infarction (fi rst or recurrent) to 13% for chronic renal insuffi ciency.…”
Section: Risk Of Adverse Events For Hypertensionsupporting
confidence: 87%
“…For example, systolic pressure has been shown to predict myocardial infarctions, strokes, renal insuffi ciency, and sudden death. [11][12][13][14][15][16][17] Diastolic blood pressure correlates with developing ischemic heart disease, 15,[17][18][19][20] sometimes with a J-shaped distribution. 15,20,21 Heart rate predicts cardiovascular death, 22,23 while increased pulse pressure predicts heart failure.…”
Section: Risk Of Adverse Events For Hypertensionmentioning
confidence: 99%
“…Pekkanen et al 29 studying 1619 men aged 40-59 years at baseline, found that SBP was no longer associated with CAD risk after 20 years of follow-up, when subjects had become elderly, and the Framingham study in a recent re-analysis, 30 concluded that CAD mortality does not depend on SBP in a linearly increasing manner. In the recent analysis of Alli et al, 31 DBP was not an indicator of mortality risk in the elderly. This is also in agreement with previous observations [32][33][34][35][36] suggesting a limited effect of antihypertensive treatment in the prevention of CAD in elderly people.…”
Section: Sbp and Dbp Unpredictive Of Cad Mortalitymentioning
confidence: 88%
“…The National Health and Nutrition Examination Survey (NHANES II) study by Pastor-Barriuso and the SPAA (Studio sulla Pressione Arteriosa nell'Anziano) Italian BP measurement study 24 both noted a linear, graded, and consistent relationship between systolic pressure and the incidence of CVD events. These studies also failed to note a linear relationship between DBP and CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have noted a linear relationship between both systolic and diastolic blood pressure (SBP and DBP) and cardiovascular disease (CVD) event rates in the elderly, 6,7 a linear SBP association and a J-shaped DBP relationship has been noted with CVD events in other studies. 8,9 In the elderly, some disagreement has surrounded the importance of monitoring and treating SBP, DBP, or both, as well as whether to treat isolated and/or borderline isolated systolic hypertension.…”
Section: Introductionmentioning
confidence: 99%